2000
DOI: 10.1542/peds.105.4.e45
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Trial of the Effects of Prophylactic Theophylline on Renal Function in Term Neonates With Perinatal Asphyxia

Abstract: Our data suggest that prophylactic theophylline, given early after birth, has beneficial effects on reducing the renal dysfunction in asphyxiated full-term infants. (ABSTRACT TRUNCATED)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
1
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 30 publications
6
78
1
5
Order By: Relevance
“…When related to the results of Gouyon and Guignard (4) with the same model, it appears that the nonspecific inhibition with theophylline was more likely to protect renal function in the neonatal period, as theophylline totally prevented the hypoxemia-induced vasomotor nephropathy in the newborn rabbit. Furthermore, theophylline significantly increased urine output and creatinine clearances in neonates with acute renal insufficiency due to respiratory distress syndrome (12) or perinatal asphyxia (13), as in diuretic-dependent critically ill children aged 1 wk to 17 y (14). As in the normoxic group, an increased renin release from the JG cells might have occurred after DPCPX administration, and adenosine-induced endothelin release in the kidney might also be involved.…”
Section: Map Heart Rate (Hr) Hematocrit (Htc) Plasma Protein Levmentioning
confidence: 90%
See 1 more Smart Citation
“…When related to the results of Gouyon and Guignard (4) with the same model, it appears that the nonspecific inhibition with theophylline was more likely to protect renal function in the neonatal period, as theophylline totally prevented the hypoxemia-induced vasomotor nephropathy in the newborn rabbit. Furthermore, theophylline significantly increased urine output and creatinine clearances in neonates with acute renal insufficiency due to respiratory distress syndrome (12) or perinatal asphyxia (13), as in diuretic-dependent critically ill children aged 1 wk to 17 y (14). As in the normoxic group, an increased renin release from the JG cells might have occurred after DPCPX administration, and adenosine-induced endothelin release in the kidney might also be involved.…”
Section: Map Heart Rate (Hr) Hematocrit (Htc) Plasma Protein Levmentioning
confidence: 90%
“…Moreover, in neonates with respiratory distress syndrome (12) or perinatal asphyxia (13), as in diuretic-dependent critically ill children (14), the use of theophylline improves diuresis and creatinine clearance. Specific adenosine receptor antagonists are now available for clinical use (15).…”
mentioning
confidence: 99%
“…Several independent randomized studies in asphyxiated infants have shown that prophylactic theophylline, given early after birth, was associated with better kidney function. [70][71][72][73] As a result, the KDIGO guidelines recommend a single dose of theophylline for asphyxiated infants at risk for AKI. 44 Caution must be taken, as theophylline has some potentially harmful neurologic effects.…”
Section: Neonatal Cardiac Surgerymentioning
confidence: 99%
“…3 Jenik dkk melaporkan pemberian teofolin 8 mg/kgbb yang diberikan beberapa jam setelah lahir pada neonatus cukup bulan dengan asfiksia berat secara bermakna dapat menurunkan kreatinin serum dan b2-mikroglobulin urin, serta terjadinya peningkatan klirens kreatinin. 25 …”
Section: Dampak Terhadap Ginjalunclassified